Effectiveness of Collaborative on Learning Among Gen Z Engineering Students - Dass, Sandhya; H. S., Ramananda; B., Jagadeesha; P. C., Rajesh Kumar; Cherian, Reni K. K (Journal of Engineering Education Transformations, 2021)
Collaborative learning helps to get the most out of students’ academic as well as intellectual capabilities by engaging a team of students in self-regulated learning activities under the supervision of course coordinators. At the swipe of a screen, Generation Z (Gen Z) has the solutions to every problem. The need to promote interactive and productive learning and to cater to the needs of current Generation Z (Gen Z) engineering students, collaborative learning is considered to be one of the most profound approaches which can be incorporated in the teaching and learning process on the campuses. The aim of this research is an attempt to understand the engineering students’ insights towards collaborative learning and its effectiveness. The study population of this action research is the second-year electronics and communication engineering students (N=60; males=33; females=27) on a core course at St Joseph Engineering College, Mangaluru, Karnataka, India. They were selected on the basis of their performance in the previous test. The collaborative activity was conducted in two phases. Six Thinking Hats activity was adopted for collaborative learning activity. A detailed research design with a structured questionnaire has been used to measure the effectiveness of the activity. Collaborative learning is found to be an effective method in enhancing learning among Gen Z engineering students, with a positive correlation-between collaborative learning and student performance and the assessment parameters of the presentation indicate that the students participated actively.